Quarries of the Kunów surroundings as future geotourist attractions within the Kamienna Valley Geopark - Gałka, Elżbieta (Geotourism/Geoturystyka, 2014)
In this paper, Liassic and Triassic sandstone quarries of the Kunów surroundings were described as future geotourist attractions within the planned Kamienna Valley Geopark. The history of sandstone excavation from medieval ages to the contemporary period and their usage in regional/local, sacral, monumental, defense as well as industrial architecture were included. Representative, geological, geomorphological and tourist attractions of the quarries and their surroundings were described, marked out and connected in order to create valuable educational and landscape geotourist trail. After implementation of the proper tourist infrastructure, especially accommodation, as well as undertaking marketing efforts in order to promote the centuries-old quarrying centre, Kunów has a chance to become another, besides Jura Park Bałtów and Krzemionki flint mine, very important geoeducational and recreational centre within the north-eastern margin of the Holy Cross Mts.